2007
DOI: 10.1002/eji.200737270
|View full text |Cite
|
Sign up to set email alerts
|

TREM‐1 expression in macrophages is regulated at transcriptional level by NF‐κB and PU.1

Abstract: Triggering receptor expressed on myeloid cells (TREM)‐1 is a recently identified immunoglobulin receptor that is expressed on neutrophils and monocytes where it amplifies the acute inflammatory response to bacteria. We examined the transcriptional regulation of TREM‐1 in macrophages. Treatment of RAW cells with Escherichia coli LPS or Pseudomonas aeruginosa led to the induction of TREM‐1 within 1 h with an expression lasting up to at least 24 h in vitro as detected by RT‐PCR. Since the promoter of TREM‐1 has m… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

9
78
0
3

Year Published

2009
2009
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 84 publications
(92 citation statements)
references
References 46 publications
(54 reference statements)
9
78
0
3
Order By: Relevance
“…This validation is particularly important in light of a recent gene expression profiling comparison between human and mouse monocyte subsets, which revealed that among the most striking differential expressions was that of TREM-1 (Ingresoll et al, 2010). In agreement with the findings above, up-regulation of TREM-1 gene expression has also been shown in RAW 264.7 cells challenged with either Escherichia coli LPS, or Pseudomonas aeroginosa, and this effect was sustainable over 48 h (Zeng et al, 2007). Nevertheless, in another study it was demonstrated that E. coli LPS does not affect TREM-1 transcription in peripheral blood monocytes, but causes an increase in cell surface TREM-1 expression, denoting an effect on post-transcriptional modulation (Wong-Baeza et al, 2006).…”
Section: Discussionsupporting
confidence: 91%
See 1 more Smart Citation
“…This validation is particularly important in light of a recent gene expression profiling comparison between human and mouse monocyte subsets, which revealed that among the most striking differential expressions was that of TREM-1 (Ingresoll et al, 2010). In agreement with the findings above, up-regulation of TREM-1 gene expression has also been shown in RAW 264.7 cells challenged with either Escherichia coli LPS, or Pseudomonas aeroginosa, and this effect was sustainable over 48 h (Zeng et al, 2007). Nevertheless, in another study it was demonstrated that E. coli LPS does not affect TREM-1 transcription in peripheral blood monocytes, but causes an increase in cell surface TREM-1 expression, denoting an effect on post-transcriptional modulation (Wong-Baeza et al, 2006).…”
Section: Discussionsupporting
confidence: 91%
“…Individual microbial components, such as lipopolysaccharide (LPS) and peptidoglycan, can cause up-regulation of cell surface-localized TREM-1 by monocytes, as well as release in its soluble (s)TREM-1 form (Begum et al, 2004;Gibot et al, 2004b;Gomez-Pina et al, 2007;Murakami et al, 2007;Ramanathan et al, 2005;Zeng et al, 2007). The sTREM-1 appears to be released during the course of infection, and may well be a particularly useful marker of systemic inflammation, as demonstrated in systemic sepsis, septic arthritis, pneumonia (Collins et al, 2009;Gibot et al, 2005;Gibot et al, 2004a;Gibot et al, 2004c;Knapp et al, 2004).…”
Section: Introductionmentioning
confidence: 99%
“…Their study suggests that activation of TREM-1 in response to LPS is related to production of PGE2 in macrophages [23]. In a recent study, we have shown that the TREM-1 gene is regulated at a transcriptional level by NF-kB, PU.1 and AP1 in macrophages in response to LPS [26]. This study for the first time shows that expression of TREM-1 in response to LPS and LTA requires the presence of TLR and indicates that the expression of TREM-1 in response to LTA and LPS occurs as a result of activation of TLR.…”
Section: Discussionmentioning
confidence: 89%
“…For example, NF-kB is activated by the TLR signaling pathway. We have shown that activation of TREM-1 is dependent on NF-kB activation [26]. In addition TREM-1-mediated tyrosine phosphorylation, activation of MAPK, and mobilization of Ca 21 might also lead to the activation of transcription complexes, which could have a synergistic effect with NF-kB in promoting the expression of pro-inflammatory genes.…”
mentioning
confidence: 92%
“…We have shown that the functional consequences of TREM-1 silencing in macrophages include an altered availability of key signaling (CD14, IB␣, and MyD88), and effector molecules (MCP-1, IL-1␤, and IL-6) downstream of TLR activation. Furthermore, the presence of TLRs is necessary for the expression of TREM-1 in response to specific TLR ligands (15)(16)(17). These receptors have thus emerged as potent amplifiers of TLR-initiated inflammatory responses (14,16,18).…”
mentioning
confidence: 99%